“People would have died.” How the involvement of community pharmacy in COVID-19 vaccination was delayed: A multi-method policy implementation case study of Ireland (Dec 2020 to June 2021) - Koay, Aaron (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Sociology, 2022)
Introduction: When the National COVID-19 Vaccination Programme began in Ireland, there was a delay in involving community pharmacy despite its role being outlined in the associated Strategy and Implementation Plan. Aim and Objective: I aimed to explore how the policy implementation process was delayed, framed between 15th Dec 2020 (publication of the Strategy and Implementation Plan) and 14th June 2021 (commencement of vaccination by community pharmacies). My objective was to understand how policy dynamics like institutional structures, power, politics and actors shaped the implementation process. Conceptual Framework: I used the Five-stream Framework to inform my analytic thinking, especially for documentary analysis. Methodology: Situated in a Big Q paradigm and through a critical realist lens, I reflexively carried out a multi-method case study: 1) I used stakeholder involvement to guide my methodology design; 2) I analysed 190 systematically scoped documents by directed qualitative content analysis against the Five-stream Framework to inform my interview topic guide, clarify the timeline and identify relevant policy actors; and 3) I undertook semi-structured elite interviews with eleven policy actors and approached the data using reflexive thematic analysis. My analysis shifted between deductive and inductive, critical and experiential as well as semantic and latent modes; and 4) I integrated and situated my data within the literature to develop a complex and multi-dimensional analysis. Analysis: I developed three themes: 1) In “On a rational basis”, I illustrated that the delay was inevitable due to significant operational barriers that impeded the role of community pharmacy. This was supported by two sub-themes, i.e. “When was the right time?” and “Not to take chances with the vaccine”, which respectively dealt with efficiency and safety aspects of the operation; 2) In “[Nonsense] and obfuscation” I articulated that the perceived operational challenges was unjustifiable and was based on a perceived deficit of the profession; 3) In “Politics with a small p”, I articulated that the chronic lack of the ability of the (community) pharmacy sector to influence health policies was because “Pharmacy has shot itself in the foot” - a lack of strategic leadership and cohesion - and “Doctor knows best” - the strong dominance of the medical profession and their political leverage to influence health policies. Conclusions: My research elucidated a highly complex and politicised policy implementation process shaped by socio-political, institutional, regulatory and technical factors, which was arguably driven by a chronic lack of clear and strategic direction for pharmacy in the health system.
Keywords: COVID-19; Vaccination; Community Pharmacy; Ireland; Health Policy; Health Politics; Pharmacy Practice